Support for co-operation between scientifi c institutions and enterprises as an instrument of Polish innovation policy - Bajak, Łukasz; Weber, Sebastian (Journal of Public Governance, 2012)
The aim of the article is to review the conclusions and recommendations regarding the directions of implementation of Poland’s innovation policy to support co-operation between scientific institutions and enterprises. The authors discuss the theoretical signifi cance of co-operation between science and business for the innovation process and transfer of technology, as well as its indirect impact on economic growth and competitiveness of the national economy. The article also describes the foundations and instruments of Poland’s innovation policy in support of co-operation between scientific institutions and enterprises, and details the difficulties inherent in such co-operation. Following up on the conclusions resulting from the material discussed, the authors recommend activities aimed at improving the cooperationbetween science and business.